ANALISIS PENGARUH FAKTOR INTERNAL PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Ahmad Ridho Fachrizal Chaery (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
This research was conducted to test the influence of Internal Factors such as Liqudity, Activity, Solvability, Profitability and Company’s Growth to the Stock Price. The object of this research is a manufacturing company of food and beverage sectors listed in Indonesia Stock Exchange in the period 2013 to 2017. This study uses multiple linear regression analysis that begins with the classical assumption, using a sample of 11 companie of food and beverage sector. The results obtained from this study is partially Solvability and Profitability has an influence on Stock Price, While Liquidity, Activity and Company’s Growth do not affect significantly to Stock Price. Simultaneously the results obtained are all independent variables (Liqudity, Activity, Solvability, Profitability and Company’s Growth) jointly have a significant effect on Stock Price.